The Expansion Input a Output Tables - Dr. Bui Trinh; Kiyoshi Kobayashi; Le Hoa Pham (Global Journal of Human-Social Science, 2012)
This paper is an attempt in order to present some variance of input-output expansion The System of National Accounts with version 1968 and 1993 recommended on social accounting matrix but until now some countries compiled SAM from supply and use tables and some other countries compiled SAM from input-output system SAM seems to apply for CGE model but it is not meaning in SAM multipliers analysis The parallel with ideas of social accounting system developed by Stone 1961 Pyatt and Roe 1977 is demographic-economic modeling was knew by Miyazawa s concept These ideas developed in order to describe the interrelation between income from production income from redistribution consumption accumulation it like as no start and no the end in Buddha theory